(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The research aims to identify banking stress tests, which is one of the modern and important tools in managing banking risks by applying the equations of that tool to the sample. The banking sector considered one of the most vulnerable to sudden and rapid changes in an unstable economic environment, making it more vulnerable. Therefore, it is necessary to establish a special risk management section to reduce the banking risks of the banking business that negatively affect its performance. The research concluded that there is a direct relationship between stress tests and risk management, as stress tests are an essential tool in risk management. They also considered a unified approach in managing bank risks that helps the bank to detect the impact of the bank’s risks and the bank’s ability to face these risks, in order to maintain the soundness of the bank’s financial position and its ability to continue the banking business. Thus, the supervisory authority should develop a unified methodology for stress tests so that banks can apply them, take advantage of this important tool in the management of banking risks, and avoid the shocks that may exposed to banks.